The influence of radiofrequency/microwave energy absorption on physiological regulation. - Michaelson, S. M. (Nature Publishing Group, 1982)
Physiological regulation represented by thermoregulation, neuro endocrine function, neurochemical activity, and immune responses is a composite of exquisitely "tuned" interrelated systems that constitute sensitive indicators of body responses to environmental stimuli or absorbed physical energies. Exposure to microwave/radiofrequency fields may affect such physiological regulation. Study of the integration and correlation of many body functions relative to the altered homoeostatic status of the microwave/radiofrequency-exposed subject is thus indicated. Microwave-induced physiological changes cannot be dissociated from increases in tissue temperature. Such responses are considered to be essential in defence against environmental changes as a febrile response is essential for host immune defence. These responses can also be considered to reflect the utilization of physiological function to maintain regulations or adjustments. These are not necessarily adverse reactions to environmental stimuli. These responses can be transient or persistent, beneficial or detrimental. Assessment of the integration and correlation of these functions relative to the thermal inputs and homoeokinetic reactions of the individual subjected to microwave/radiofrequency energy should permit differentiation between potential hazards which might compromise the individual's ability to maintain normal physiological function and effects which are compensated by physiological redundancy.